Pengaruh Kompetensi dan Budaya Organisasi Terhadap Kinerja Pegawai Pada Badan Pengelola Keuangan Daerah Kabupaten Enrekang - Junedi G; Abdi Akbar; Uhud Darmawan Natsir; Chalid Imran Musa; Burhanuddin (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2023)
The purpose of this study was to determine the influence of competence and organizational culture on employee performance at the Regional Financial Management Board of Enrekang Regency. The population in this study were all employees at the Regional Financial Management Agency of Enrekang Regency as many as 75. The type of research used was quantitative research. The data used are primary data and secondary data obtained using a questionnaire distribution technique. The results of data processing research using SPSS.24 show that based on the results of Multiple Linear Regression analysis there is a positive influence between Competency (X1) and Organizational Culture (X2) variables on Employee Performance which can be shown through the multiple linear regression equation, namely Y = 14.390 + 0.302 X1 + 0.087 X2 + e and there is a significant influence between Competency and Employee Performance variables, which can be seen from the Sig value. of 0.017 <0.05 or in other words the significant value is smaller than the error level (0.05). While the Organizational Culture Variable has no significant effect on Employee Performance which can be seen from the Sig. equal to 0.479 > 0.05 or in other words the significant value is greater than the error level (0.05). The R Square value of 0.143 indicates that the Employee Performance variable is influenced by Competence and Organizational Culture by 14.3% while the remaining 85.7% is influenced by other variables not examined in this study.